Optimal attitude control and maneuver design for space debris detection in low earth orbit performed by a CubeSat - Aldana Afanador, Andres Felipe (UiT Norges arktiske universitet, 2024)
Space debris has become an important topic, and several national and international space agencies are currently studying space debris detection and removal to increase the safety of space missions. UiT the Arctic University of Norway in Narvik is aiming to develop a 2U CubeSat that can perform in-situ detection of debris with the projects UNICube and QBDebris. The mission target is to detect mm-sized debris that cannot be detected from groundbased systems; detection will be done by radar technology. The main challenge of the mission relies on the small size and high velocity of the objects, for which the satellite must have the capacity for quick reaction in the pointing angle with a precise attitude controller without spending a high cost in energy. The main goal of this work is to develop novel attitude maneuvers for debris detection. The satellite is programmed with three procedures. Debris detection scanning: The control system was designed with high relative importance on the state’s performance and moderate input penalty. This allows the radar to scan while the CubeSat is pointing to a desired angle. However, due to the high speed of the objects, false positive detections exist. Validation process: The detected objects will be scanned inside the radar region, and it is possible to approximate the position in which the debris can be spotted after the first detection. The debris validation maneuver gives the satellite the ability to perform more aggressive maneuvers by lowering the penalty on the input changes. This maneuver is designed for angular trajectory tracking in which the CubeSat performs a controlled rotation that allows the radar to maintain the object inside of the detection volume for a longer period, obtaining more information regarding the debris. Charging process: This procedure is developed for solar panels to maximize energy acquisition using a high input penalty, minimizing energy costs. Achieving adequate attitude control significantly impacts the performance of the detection tasks. ...